2001
DOI: 10.1177/0743558401163004
|View full text |Cite
|
Sign up to set email alerts
|

Interparental Conflict and Family Cohesion

Abstract: Family environment is related to characteristics of adolescents’ personal development and social interactions. Although potentially different for males and females, decreased family cohesion and increased interparental conflict can inadvertently provide family environments that are associated with increased feelings of loneliness, which may be associated with problems in adolescents’ social interactions (i.e., social anxiety and social avoidance). Analyses of responses from 124 late adolescents revealed that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(40 citation statements)
references
References 26 publications
2
35
0
3
Order By: Relevance
“…For example, Johnson, et al, and Maccoby (29,30) demonstrated that low family cohesion was related to feelings of exclusion, isolation, and loneliness for females. Since this study did not aim to investigate gender differences, our findings must be interpreted cautiously.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, Johnson, et al, and Maccoby (29,30) demonstrated that low family cohesion was related to feelings of exclusion, isolation, and loneliness for females. Since this study did not aim to investigate gender differences, our findings must be interpreted cautiously.…”
Section: Limitationsmentioning
confidence: 99%
“…Aspects of the parent-child relationship have been frequently studied, with many studies focusing on parent-child conflict or parenting style (Steinberg and Morris 2001). A large number of studies have examined the effect of marital (interparental) conflict on children's adjustment, consistently demonstrating the relationship between marital conflict and adjustment over time (e.g., Fincham 1994;Grych et al 2004;Johnson et al 2001), including findings that children's emotional insecurity about interparental conflict mediate adjustment (Cummings et al 2006). The risk for developing problems associated with marital conflict is present for all families, including non-clinical families (Cowan et al 1996).…”
mentioning
confidence: 98%
“…H 2 : It was hypothesized that higher levels of family cohesion would buffer (i.e., negatively moderate) the effect of anxiety on IGD symptoms over time (Kaur & Kearney 2013;Ibanez et al 2015;Johnson et al 2001;Priest & Denton, 2012).…”
Section: The Present Studymentioning
confidence: 99%